A call for an epistemic look at inconsistencies between ESL/ESL teachers' beliefs and teaching practice - Tehrani, Hesam Tahsildar; Mohamed Razali, Abu Bakar (Human Resource Management Academic Research Society, 2017)
Almost all previous research on ESL/ESL teachers’ stated beliefs is indicative of little or partial correspondence between what ESL/EFL teachers believe about teaching and what they do in class. Phipps and Borg (2009) attribute the cause of this inconsistency to the lack of close attention to the differences between teachers’ core and peripheral beliefs in research on teaches’ beliefs. Core beliefs are fundamental to an individual’s belief system, associated with other beliefs, and are impervious to transformation and modification. On the other hand, peripheral beliefs are derivatives of core beliefs and are comparatively more easily modified. The little attention to the distinction between ESL/EFL teachers’ core and peripheral beliefs can potentially result in recurring inconsistencies between teachers’ stated beliefs and their teaching practice in future studies. This paper, therefore, suggests that epistemic beliefs (a system of more-or-less independent beliefs about knowledge and learning; Schommer, 1990) be used in future studies in eliciting ESL/EFL teachers’ core beliefs. It is argued that epistemic beliefs elicitation provides researchers with teachers ‘core and peripheral beliefs. In addition, teachers’ core and peripheral beliefs and their relation to epistemic beliefs will be delineated.